Cash Transfers in Latin America: Effects on Poverty and Redistribution. - AMARANTE, VERÓNICA; BRUN, MARTÍN (Economía)
We present comparative evidence for eight Latin American countries regarding the design and effects of cash transfers (CTs). On the basis of household survey data, we analyze their coverage, importance in household income, and effects on poverty reduction and income redistribution. We present a static microsimulation to analyze the potential impacts of alternative program designs, including perfect targeting and higher budgets. Our results illustrate wide variation in terms of design, coverage, and importance in household income. CTs account for a significant portion of household income in lower deciles. Nonetheless, their effects in terms of reducing the incidence, intensity, and severity of poverty are moderate at best, and although their progressivity is high, their redistributive impact is limited. These results are mainly explained by the meager resources involved. Even under perfect targeting, the budgets allocated would be insufficient to achieve full coverage among households in the lowest part of the income distribution.